Israeli Occupation Violations of the Right to Bodily Integrity in the Palestinian Territories in Light of International Law - Al-Wardat Naif Hassan , Imad; Chergui, Salaheddine (Journal of Legal Studies and Researches, 2026)
The study aimed to identify the most significant violations committed by the Israeli occupation against the right to bodily integrity in the Palestinian territories, in light of international law. The research adopted the descriptive analytical approach and was structured into sections and subtopics. The study concluded that the Palestinian people's struggle against the Israeli occupation constitutes a national liberation war, and as such, it is classified as an international armed conflict subject to the full body of the laws of war.